Avaliação de sistema de drenagem em final de rede pluvial em Campo Mourão – PR - Pavezzi, Bárbara Regina Delconte Ferreira (2022)
The accentuated growth of urban centers causes, among other implications, changes in land use and occupation, significantly increasing impermeable areas and suppressing natural vegetation, inhibiting water infiltration, reducing water table recharge, generating acceleration and volumetric increase of the surface runoff. Thereby the water reaches the receiving points with high velocity, flow and energy in a short period of time, causing an overload of the receiving points when intense precipitation occurs. The correct traditional drainage system’s design is extremely important to reduce the possible impacts, especially when associated with structural control measures compatible with the associated watershed. Thus, this work aims to evaluate the hydraulic performance of a wathershed’s drainage system in the city of Campo Mourão, Paraná. To do so, the necessary data were obtained using the rational method combined with the method described by Menezes Filho and Costa (2012) to verify the pipes’ dimensioning and flow attributes. The viability of applying a Sustainable Urban Drainage System was also investigated. Differences were identified in the evaluated diameters and also the need for complementary structures due to the flow features. As for the application of a sustainable device, it was found that the area available for implementation would be insufficient.